Evaluation of the Antiviral Activity of Chlorine Dioxide and Sodium Hypochlorite against Feline Calicivirus, Human Influenza Virus, Measles Virus, Canine Distemper Virus, Human Herpesvirus, Human Adenovirus, Canine Adenovirus and Canine Parvovirus - SANEKATA, TAKESHI; FUKUDA, TOSHIAKI; MIURA, TAKANORI; MORINO, HIROFUMI; LEE, CHEOLSUNG; MAEDA, KEN; ARAKI, KAZUKO; OTAKE, TORU; KAWAHATA, TAKUYA; SHIBATA, TAKASHI (Biocontrol Science, 2010)
We evaluated the antiviral activity of a chlorine dioxide gas solution (CD) and sodium hypochlorite (SH) against feline calicivirus, human influenza virus, measles virus, canine distemper virus, human herpesvirus, human adenovirus, canine adenovirus and canine parvovirus. CD at concentrations ranging from 1 to 100 ppm produced potent antiviral activity, inactivating ≥ 99.9% of the viruses with a 15 sec treatment for sensitization. The antiviral activity of CD was approximately10 times higher than that of SH.